Physics of the dynamic ergodic divertor - Jakubowski, M.W.; Finken, K.H.; Abdullaev, S.S.; Kobayashi, M.; Lehnen, M.; Wolf, R. (Вопросы атомной науки и техники, 2002)
The Dynamic Ergodic Divertor (DED) of TEXTOR is presently being installed. It consists of sixteen helically wound coils occupying about 30% of the wall at the HFS. The coils follow field lines on a “pre-selected” magnetic surface and are fed individually outside the vessel. A perturbation field is created by the electrical currents in the perturbation coils with Fourier components resonant to the magnetic surfaces. The stochastic boundary layer is generated in the outermost region of the plasma, which due to long and short connection lengths can be divided into ergodic and laminar regions. Field line tracing and mapping techniques were used to analyse properties of the TEXTOR-DED plasma boundary. The DED will operate with several frequencies (DC or AC up to 10 kHz). In the “dynamic” operation the convective heat flux is deposited to a large plasma-facing surface and forces are transferred to the plasma edge, what can introduce a differential rotation of the plasma.